Water Transport in Unsaturated Cracked Concrete under Pressure - Yuanzhu Zhang; Siming Zhang; Gang Wei; Xinjiang Wei; Liqiao Jin; Kuixin Xu (Advances in Civil Engineering)
In order to analyze the process of hydraulic water infiltrating cracked concrete of underwater tunnels, the equation of water transport in unsaturated cracked concrete under pressure was proposed according to the double-porosity medium model. Penetration tests on prefabricated cracked concrete blocks were conducted, and then the influence of hydraulic pressure, initial saturation, and crack width on water transport was studied. The results show that the larger the water pressure, the lower the initial saturation, and the wider the crack width, then the greater the penetration depth, which can be reasonably explained according to water motion theoretical models in this study. Moreover, the TOUGH2 software was used to simulate the change and distribution of saturation, driving potential, and water velocity of unsaturated cracked concrete, which further proved the experimental results and theoretical analysis. It reflects that both pressure potential and matric potential are the driving force of water transport in underwater cracked concrete, and the driving force will be converted with the change of concrete saturation. In addition, crack width is positively correlated with concrete permeability.